Digital Learning Ecosystem: Current State, Prospects, and Hurdles - Belessova Damira; Ibashova Almira; Bosova Lyudmila; Shaimerdenova Guldana (De Gruyter, 2023)
The article is an analysis of the current topic - digitalization of the educational process. In the course of collecting and interpreting the known data, the authors cite the pedagogical foundations of digital literacy, the current state of digital learning and problems, and the prospects for the development of this direction in the future are also considered. In addition, the situations of creating a digital ecosystem in individual countries of the world were analyzed.